Seasonal variation in the density of the macrophyte Scirpus cubensis Poepp & Kunth (Cyperaceae) in the Lagoa do Infernão, state of São Paulo, Brazil - Pompêo, M. L.M. [UNESP]; Moschini-Carlos, V. [UNESP] (My University, 1996)
This paper deals with the seasonal density dynamics of the macrophyte Scirpus cubensis Poepp & Kunth (Cyperaceae) in the Lagoa do Infernão, a lake marginal to the Mogi-Guaçu river, State of São Paulo, Brazil. Seasonal density dynamics of the macrophyte were studied in permanent plots of I m length by 25 cm width, divided into four subplots of 25 x 25 cm. An individual of S. cubensis was defined as an independent morphological unit arising from a rhizome node. Seasonal variation in density, with a range from 135.52 ± 171.52 to 270.00 ± 196.00 ind.m-2, is related to the drought and flood conditions to which the lake is subject. Analysis of data also suggests that 12 sample units are significant for assessment of population density. Aspects of the macrophytes sampling are also discussed. © Asociación Española de Limnología,.
Keywords: Density; Macrophyte; Scirpus cubensis